2010
DOI: 10.1158/1078-0432.ccr-10-1113
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Receptors for Luteinizing Hormone-Releasing Hormone (LH-RH) in Prostate Cancers following Therapy with LH-RH Agonists

Abstract: Purpose: In addition to their expression on pituitary cells, receptors for luteinizing hormone-releasing hormone (LH-RH) are found on most prostate cancer cells. These tumoral LH-RH receptors mediate the direct cytotoxic effects of LH-RH analogs and are potential therapeutic targets. Although pituitary LH-RH receptors are downregulated following prolonged exposure to LH-RH agonists, there is no evidence that tumoral receptors behave in a similar manner. To better characterize expression of tumoral LH-RH recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Such a strategy may overcome off-target toxicity in tandem with continuous efficacy due to persistent expression of the GnRH-R on prostate cancer cells, despite prolonged exposure to GnRH agonists (6). A better understanding of prostate cancer Figure 6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such a strategy may overcome off-target toxicity in tandem with continuous efficacy due to persistent expression of the GnRH-R on prostate cancer cells, despite prolonged exposure to GnRH agonists (6). A better understanding of prostate cancer Figure 6.…”
Section: Discussionmentioning
confidence: 99%
“…This idea is based on the evidence that certain cell surface receptors in malignant cells are either mutated or overexpressed (e.g., EGFR, HER2/neu, GnRH-R), compared with normal cells (4)(5)(6) and that these alterations provide "druggable" opportunities. We recently demonstrated the successful targeting of gonadotropin-releasing hormone receptor (GnRH-R) in GnRH-R-positive prostate cancer using a conjugate of a GnRH peptide linked to the cytotoxic drug gemcitabine (7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While expression of LHRH receptors may not be common in normal, nonpituitary tissue, these receptors are highly expressed on malignant tissue, including cancers of the lung, ovary, endometrium, bladder, kidney, breast, colon, and prostate (7)(8)(9)(10)(11)(12)(13)(14)(15). We have previously reported that expression of LHRH receptor on prostate cancer cells persists despite prolonged exposure to LHRH agonists (16).…”
Section: Introductionmentioning
confidence: 99%
“…In this limited study of 17 patients, 3 achieved a partial or complete response and 4 achieved stable disease. Given the persistent expression of LHRH receptors in prostate cancer cells (16) and the lack of expression on most normal tissues, AEZS-108 represents a promising targeted therapeutic agent for CRPC. Because the experience with AEZS-108 was limited to female patients, we designed a dose-escalation study of AEZS-108 in men with CRPC before launching a phase II trial (NCT01240629).…”
Section: Introductionmentioning
confidence: 99%